2023
DOI: 10.1111/cns.14253
|View full text |Cite
|
Sign up to set email alerts
|

Increasing brain N‐acetylneuraminic acid alleviates hydrocephalus‐induced neurological deficits

Zhangyang Wang,
Xiaoqun Nie,
Fang Gao
et al.

Abstract: AimsThis metabolomic study aimed to evaluate the role of N‐acetylneuraminic acid (Neu5Ac) in the neurological deficits of normal pressure hydrocephalus (NPH) and its potential therapeutic effect.MethodsWe analyzed the metabolic profiles of NPH using cerebrospinal fluid with multivariate and univariate statistical analyses in a set of 42 NPH patients and 38 controls. We further correlated the levels of differential metabolites with severity‐related clinical parameters, including the normal pressure hydrocephalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…Studies have shown that sialic acid is essential for neonatal brain neurodevelopment and immune system development because neonates cannot synthesize it themselves and supplement it mainly through exogenous sources . Recent studies have shown that sialic acid can inhibit astrocytic proliferation, promote the polarization of A1 to A2 astrocytes, reduce demyelination, and attenuate neurological deficits induced by hydrocephalus, promoting its use in new therapeutic strategies for normal-pressure hydrocephalus …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that sialic acid is essential for neonatal brain neurodevelopment and immune system development because neonates cannot synthesize it themselves and supplement it mainly through exogenous sources . Recent studies have shown that sialic acid can inhibit astrocytic proliferation, promote the polarization of A1 to A2 astrocytes, reduce demyelination, and attenuate neurological deficits induced by hydrocephalus, promoting its use in new therapeutic strategies for normal-pressure hydrocephalus …”
Section: Results and Discussionmentioning
confidence: 99%
“…16 Recent studies have shown that sialic acid can inhibit astrocytic proliferation, promote the polarization of A1 to A2 astrocytes, reduce demyelination, and attenuate neurological deficits induced by hydrocephalus, promoting its use in new therapeutic strategies for normal-pressure hydrocephalus. 17 The O-glycan core structures of DC and DM MFGM glycoproteins were further observed. As shown in Figure 3A,B, both DC and DM MFGM glycoprotein O-glycans were predominantly mucin-type core structures, with 38.56% core-2 glycans, 25.77% core-4 glycans, 19.67% core-3 glycans, and 14.16% core-1 glycans in DC and 28.89% core-2 glycans, 25.1% core-4 glycans, 23.39% core-1 glycans, and 21.14% core-3 glycans in DM.…”
Section: Analysis Of O-glycans In DC and Dm Mfgm Glycoproteinsmentioning
confidence: 97%